An overview of the Chloropidae (Diptera) of Saudi Arabia - Dawah, Hassan A.; Abdullah, Mohammed A.; Deeming, John C. (Zootaxa, 2020)
Chloropidae are of major economic importance, since the larvae of some species are pests of cereals and grasses, some are parasitoids and predators, and adults of some Hippelates spp. visit and transmit or are suspected of transmitting yaws sores in man and animals and by feeding around the eyes are vectors of Brazilian Purpuric Fever. Within the framework of the exploration of the biodiversity of Diptera in Southwest Saudi Arabia a survey of the grass flies fauna in 18 sites in Jazan, Asir, and Najran in south-western Saudi Arabia was performed mainly using Malaise traps and sweep nets from 2010– to 2016. Sixty six species of 43 genera and three subfamilies of Chloropidae were identified and are recorded from Saudi Arabia, 20 of them for the first time and three are described as new species: Elachiptera arabica Deeming sp. n.; Kwarea ismayi Deeming sp.n. and Tricimba turneri Deeming sp.n.. This makes the total number of Chloropidae species in Saudi Arabia 95 (including 29 species previously recorded). Seventy images are presented. The species of Chloropidae listed are predominantly of Afrotropical/ Palaearctic origin. An updated checklist of Chloropidae species of Saudi Arabia is presented.This study adds new records of Chloropidae to the Saudi Arabian Diptera fauna, which will become reference points for research detailing the systematic geographic distribution and for identifying other specimens submitted for identification. Further species will undoubtedly be discovered with more research involving collecting and rearing methods.